First-Line Use of Vemurafenib to Enable Thyroidectomy and Radioactive Iodine Ablation for BRAF-Positive Metastatic Papillary Thyroid Carcinoma - Bao D. Dao MD; Ildiko Lingvay MD, MPH, MSCS; Joseph Sailors MD; Michael Landay MD; Gabriel Shapiro MD, FACP (SAGE Publishing, 2015)
Background . Patients with metastatic or radioactive iodine refractory papillary thyroid carcinoma (PTC) have poor prognosis due to ineffective therapy for this condition beyond surgery and radioactive iodine (RAI or 131 I). BRAF mutation occurs in more than 44% of PCT. Tyrosine kinase inhibitors, the most commonly used agents for these patients, have weak BRAF inhibition activity. BRAF inhibitors have demonstrated promising efficacy in relapsed metastatic PCT after standard treatment, though they are not currently approved for this indication. Case Presentation . We present the case of a 48-year-old Hispanic male who initially presented with columnar-cell variant subtype of PTC and positive BRAFV600E mutation. The patient had widespread bulky metastases to lungs, chest wall, brain, and bone. Discussion . Initial use of vemurafenib demonstrated a 42% cytoreduction of targeted pulmonary metastases and facilitated thyroidectomy and RAI treatment. The patient achieved a durable response over 21 months in the setting of widely metastatic disease. Conclusion . Vemurafenib may be effectively used for cytoreduction in patients with bulky metastatic PTC to bridge them to thyroidectomy and RAI treatment.